Compared analysis with a high-quality genome of weedy rice reveals the evolutionary game of de-domestication - Ma, Jie; Wei, Hua; Yu, Xiaoman; Lv, Yang; Zhang, Yu; Qian, Qian; Shang, Lianguang; Guo, Longbiao (Frontiers in Plant Science, 2022)
The weedy rice (Oryza sativa f. spontanea) harbors large numbers of excellent traits and genetic diversities, which serves as a valuable germplasm resource and has been considered as a typical material for research about de-domestication. However, there are relatively few reference genomes on weedy rice that severely limit exploiting these genetic resources and revealing more details about de-domestication events. In this study, a high-quality genome (~376.4 Mb) of weedy rice A02 was assembled based on Nanopore ultra-long platform with a coverage depth of about 79.3× and 35,423 genes were predicted. Compared to Nipponbare genome, 5,574 structural variations (SVs) were found in A02. Based on super pan-genome graph consisting of a 251-accession panel, the accurate SVs were found in cultivated and weedy rice. Furthermore, the de-domestication sites of weedy rice and domestication sites of wild rice were analyzed and compared based on SVs and single-nucleotide polymorphisms (SNPs). Interestingly, an average of 2,198 genes about de-domestication could only be found by SV-FST while not by SNP-FST in divergent region. Additionally, there was a low overlap between domestication and de-domestication intervals, which demonstrated that two different mechanisms existed in these events. Our finding facilitated pinpointing of the evolutionary events that had shaped the genomic architecture of wild, cultivated, and weedy rice, and provided a good foundation for cloning of the superior allele for breeding.